Implementation during design Developing understanding about service realisation before implementation. (28th July 2017) - Overkamp, Tim; Holmlid, Stefan
Abstract: Design has been mentioned as potential support in the shift from a value-in-exchange to a value-in-use perspective that is part of servitization. However, these discussions pay little attention to the role of design(ers) for implementing 1) the change in perspective of the organisation and 2) specific (product) service systems, which are both required for successful servitization. We argue that implementation as a concept needs to be part of service design processes in order to timely articulate how to implement new services, and what resources need to be shaped in service system(s) involved for successful value co-creation. We analyse a workshop in a technology-dominant service development project and show that using a service (process) perspective and concrete cases could be a way to integrate conversations about implementation in the design phase of PSS and service development. For technology-dominant services specifically, this can uncover factors for successful integration of technology and service.